Distal motor deficit as a variant of Guillain-Barré Syndrome: case report - Perez Galdos, Proel (2020)
There are some variants of Guillain-Barré syndrome (GBS) that are so unusual, such as distal limb weakness (DL-GBS), which features weakness restricted to the distal area of limbs (wrists, hands, ankles, and toes) with preserved muscle strength in the proximal areas during the course of the disease. We report the case of a 26 year-old woman, who at two weeks before admission showed mild distal motor deficit affecting the arms and afterwards her legs, and this was associated to diarrheal disease. Physical examination showed mild distal quadriparesis, with no hyporeflexia/areflexia, and a positive Lasègue sign. Laboratory studies showed ferropenic anemia, immunological tests for commonly associated viruses, tumor markers and vitamin B12 levels were all normal. Also, CSF examination showed no alterations. Cerebral and cervical spine MRI studies were normal. Electromyography and nerve conduction velocity studies at the 10th day of the disease showed acute motor axonal neuropathy with no denervation. The benign form of presentation and progression led us to think this case is a mild GBS variant (DL-GBS), different from the usual AMAN-GBS variants, which are usually severe and have a poor prognosis.